The approach of Abdul-Ghani Al-Azdi (d. 409 AH) in his book Al-Mutawarin-The news of AlHasan Al-Basri is an example - Najlaa Kareem Mahdi (Peerian Journals Publishing, 2024)
Al-Azdi’s book “The Hidden Ones” included several accounts about the escape of famous religious scholars and political men from the oppression of Al-Hajjaj bin Yusuf Al-Thaqafi, whom historians considered to be the striking hand of the Umayyads at the time. Coincidence coincided that the historian Abdul-Ghani Al-Azdi was one of those hiding from the oppression of the ruling authorities in Egypt, which pursued the pens of The noose was tightened on the narrators and hadith scholars. Al-Azdi took advantage of the opportunity to escape and hide from Al-Hakim Bi Amr Allah the Fatimid, and he began writing his book The Hidden Ones, in which he mentioned the news of nine of the most prominent men of science and politics during the time of Al-Hajjaj .
Keywords: His Method; Al-Azdi; the hidden ones